Distribution of lignans and lignan mono/diglucosides within Ginkgo biloba L. stem. (April 2022) - Yu, Min; Aoki, Dan; Akita, Takuya; Fujiyasu, Syunya; Takada, Shunsuke; Matsushita, Yasuyuki; Yoshida, Masato; Fukushima, Kazuhiko
Abstract: To investigate the biosynthetic pathways and regulatory mechanisms of lignans in plants, the actual distributions of lignans and lignan glucosides in flash-frozen stems of Ginkgo biloba L. (Ginkgoaceae) were studied using cryo time-of-flight secondary ion mass spectrometry coupled with scanning electron microscopy (cryo-TOF-SIMS/SEM). Four lignans and four lignan glucosides were successfully characterized. Quantitative HPLC measurements were conducted on serial tangential sections of freeze-fixed ginkgo stem to determine the amount and approximate distribution of lignan and lignan glucosides. (−)-Olivil 4, 4′-di- O -β-d -glucopyranoside (olivil DG) was the most abundant lignan glucoside in ginkgo and was distributed mainly in the phloem, ray parenchyma cells, and pith. The comparative accumulation of olivil DG revealed its possible transport pathways and storage sites in ginkgo. Although not all relevant enzymes have been identified, understanding the distributions of lignan and lignan glucosides in ginkgo stems provides significant insight into their biological functions. Graphical abstract: Image 1 Highlights: Lignans and lignan glucosides were visualized by cryo-TOF-SIMS/SEM. (−)-olivil 4, 4′-di- O -β-D-glucopyranoside was the most abundant lignan glucosides in ginkgo, and was distributed mainly in the phloem region, pith, and ray parenchyma cells in the mature xylem region. (−)-olivil 4, 4′-di- O -β-D-glucopyranoside might be an important intermediate and storage form in the ginkgo lignan biosynthetic pathway. Specialised metabolites were commonly accumulated in the parenchyma cells.